The sexual political issues in Pan-Yutong’s and Shang-Wanyun’s selected short stories (权力三弄：潘雨桐与商晚筠小说的性政治秀) - CHIN (é™ˆé¢–è±), Ying Xuan (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2018)
Abstract Pan-Yutong and Shang-Wanyun have similar writing styles among Chinese Malaysian writers. Their short stories concern about the issue of sexual politics. Sexual Politics was introduced by Kate Millett in 1970s. Millett was the first scholar who argues about the neglected political aspects between men and women. By applying the concept of sexual politics, this article will focus on the sexual political issues found in short stories by Pan-Yutong and Shang-Wanyun. This article also discusses the forms and elements of sexual politics issue in Pan-Yutong’s and Shang-Wanyun’s writing styles. 摘要 在马华小说家中，潘雨桐与商晚筠在书写笔调、创作背景、文字功力等方面可谓相当近似。他们的小说也共同表现了性政治现象。“性政治”是二十世纪七十年代美国女性主义学者凯特•米利特（Kate Millett）在其同题著作中提出的概念。男性与女性之间存在着的权力不公的问题,正说明了米利特所主张的“性即是政治”。从性别的角度看来，米利特的性政治概念有助于梳理潘雨桐与商晚筠小说的性别议题。本文将从梳理性政治形式开始，进而分析形成性政治之元素，以探讨潘雨桐与商晚筠小说中的性政治秀。